2014
DOI: 10.1186/1472-6963-14-151
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation trends of rosiglitazone and pioglitazone in Australia before and after safety warnings

Abstract: BackgroundA see on cardiovascular diseases and bladder cancer. The changes to the patterns of rosiglitazone and pioglitazone utilisation in Australia following the timing of these various health authority warnings such as the Australian Therapeutic Good Administration (TGA), European Medicines Agency (EMA) press releases or U.S. Food and Drug Administration (FDA) is unknown. This study investigated the utilisation patterns of rosiglitazone and pioglitazone in Australia before and after warnings of major drug a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
3
16
3
Order By: Relevance
“…Our findings were consistent with the results described in previous studies conducted in other countries. In Canada, the number of rosiglitazone users declined substantially by 85% between 2011 and 2012; in the UK, the incidence of its use also fell steeply from 0.8/1000 person‐years to 0.2/1000 person‐years in 3 months post the publication of safety signals in May 2007, and similar trends were observed in the US, the Netherlands, and Australia . Our results suggested that clinicians and administrative authorities in Korea heeded the clinical evidence published in literature and related safety alerts communicated to the medical community, domestically and globally alike, regarding suspected serious CV risks associated with medication use.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our findings were consistent with the results described in previous studies conducted in other countries. In Canada, the number of rosiglitazone users declined substantially by 85% between 2011 and 2012; in the UK, the incidence of its use also fell steeply from 0.8/1000 person‐years to 0.2/1000 person‐years in 3 months post the publication of safety signals in May 2007, and similar trends were observed in the US, the Netherlands, and Australia . Our results suggested that clinicians and administrative authorities in Korea heeded the clinical evidence published in literature and related safety alerts communicated to the medical community, domestically and globally alike, regarding suspected serious CV risks associated with medication use.…”
Section: Discussionsupporting
confidence: 72%
“…Besides prevalent use of metformin as mono or dual therapy, of note 12 and similar trends were observed in the US, the Netherlands, and Australia. 13,17,18 Our results suggested that clinicians and administrative authorities in Korea heeded the clinical evidence published in literature and related safety alerts communicated to the medical community, domestically and globally alike, regarding suspected serious CV risks associated with medication use. Although the domestic regulations allowed conditional access, albeit heavily restricted, to rosiglitazone for only those patients whose glycemic control cannot be achieved without the TZD agent, 16 health care providers seemed to strictly comply with the safety communications as well as the FIGURE 4 Concomitancy among the most commonly prescribed antidiabetic drug classes 2007 to 2015.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…10 Despite the safety warnings issued for pioglitazone, its utilization continued in several countries without significant reduction. 11,12 In addition, pioglitazone is still considered by ADA as a useful alternative to nontolerated metformin monotherapy, with modest cardiovascular benefits. 13,14 However, individualized patient risk-benefit assessment has been advised before the use of pioglitazone.…”
Section: Introductionmentioning
confidence: 99%